The importance of nurses in coping with Covid-19 and the legacy of the Nursing Now campaign in this pandemic scenario (Research, Society and Development, 2022)
Introduction: This article aims to highlight the importance of nurses' role in combating and containing the covid-19 pandemic and the legacy left by the Nursing Now campaign, implemented in the 2018 - 2020 triennium and extended until the end of June 2021. The occurrence of the covid-19 pandemic is a milestone in this campaign, which has given rise to debates and paradigm shifts, taking on the task of having an emblematic character in the training, perception, recognition and appreciation of nurses around the world – protagonists of the struggle for healing and health in the current situation of covid-19. Objective: To verify the difficulties encountered by nurses during the pandemic, assess the impact of the Nursing Now campaign and present possible solutions. Methodology: Systematic research, involving consultation of publications already carried out in electronic media, books and articles in journals. Results and Discussion: Nurses are in the front row in the treatment of covid-19 cases, facing serious implications for their working conditions and personal safety to be recognized. Conclusion: The Nursing team needs to act with more autonomy, with well-structured theoretical and methodological foundations so that it can advance in the analyzes and in the ability to increase and humanize access to health care. The pandemic came to teach that mental health is a priority over physical health, as a healthy and balanced, strong and well-informed mind is allied in the process of treating and curing physical diseases and to face all individual, regional and regional difficulties and obstacles World.